Elmina, 'the little Europe' : European impact and cultural resilience - Adjaye, Joseph K., 1940- (Sub-Saharan Publishers, 2018)
This is a brief introduction to the history of Elmina, its castle, the people, and their traditions. It outlines the town's 500-year relations with Europeans, highlighting the transformations that have developed out of these interactions. Written by one of the top historians of Ghana and a leading scholar of the African diaspora, the book is based on original archival information and orally-derived sources. It is also richly informed by the writer's own personal knowledge as a Nyampa Safohen and citizen of Elmina. Despite the tremendous changes engendered by the European contact, Elmina's historical development demonstrates an amazing degree of cultural continuity and resilience in its political institutions, social organization, economic systems and worldview.